1. Celebrative Ethics 2. Little Traditions and National Culture 3. Poems of Life - Kalluveettil, Paul; Mundadan, A Mathias (Journal of Dharma, 2001)
1. Paulachan P. Kochappilly C.M.I., Celebrative Ethics, Bangalore: Dharmaram Publications, 1999, pp. ix+S! 1. Rs.200.00; US$ 20.00 ISBN: 81-86861-12-2. 2. Thomas Kadankavil, cmi (ed.), Little Traditions and National Culture, Bangalore: Journal of Dharma and Dharmaram Publications, 2000, pp. 325. Rs.250.00; US$18.00. 3. Sr. Cleopatra, cmc, Poems of Life (Enlarged Millennium Edition), Bangalore: Dharmaram Publications, 2000, pp. 76. Rs. 45.00; US$ 3.00.